Early and Midterm Outcome of Surgical Repair of Total Anomalous Pulmonary Venous Connection - Sandy Adel; Karam Mosallam Eisa; Mohamed Adel Elgamal; Asmaa Gaber Rizk (SVU - International Journal of Medical Sciences)
Background: The mortality rates following surgical correction of Total anomalous pulmonary venous connection (TAPVC) have shown improvement due to advancements in surgical techniques. Objectives: This work aimed to analyze the early and midterm outcomes of TAPVC single-stage surgical repair and to identify the risk of morbidity and mortality. Patients and methods: This prospective study was carried out on 27 TAPVC patients who underwent different single-stage surgical techniques. The extracardiac type was treated with side-to-side anastomosis and vertical vein ligation, while the cardiac type required cutting back to the coronary sinus, intraoperative data, postoperative course, mortality rate, and complications were collected and analyzed. Results: 27 patients with ages ranged from 0.26 to 84 months, 51.85% were males while 48.15% were females. Mortality occurred in 9 (33.33%) patients due to cardiac arrest during anesthesia induction in 1 (3.7%) patient, sepsis in 2 (7.41%) patients, LCOP in 4 (14.81%) patients and pulmonary hypertensive crisis in 2 (7.41%) patients. Postoperative complications were pneumothorax in 2 (7.41%) patients, pulmonary edema in 1 (3.7%) patient, re-intubation in 2 (7.41%) patients, pneumonia in 1 (3.7%) patient, fits in 2 (7.41%) patients, thrombocytopenia in 1 (3.7%) patient, bleeding from ETT in 1 (3.7%) patient, LCOP in 5 (18.52%) patients, pulmonary hypertensive crisis in 3 (11.11%) patients, cardiac arrest in 1 (3.7%) patient, renal failure in 1 (3.7%) patient and no complication in 14 (51.85%) patients. Re-opening occurred in 1 (3.7%) patient. Sepsis occurred in 2 (7.41%) patients. The mean postoperative bleeding was 109.8 ±77.6 ml. Conclusion: The high morbidity and mortality associated with TAPVC single-stage repair, emphasizing the need for careful preoperative evaluation and perioperative management.